Developing and Testing the Health Care Safety Hotline A Prototype Consumer Reporting System for Patient Safety Events - Schneider, Eric C. (RAND Corporation, 2016)
This report describes the design, development, and testing of the Health Care Safety Hotline, a prototype consumer reporting system for patient safety events. Reports obtained were considered useful and had little overlap with information received through health care organizations' monitoring systems, but the frequency of reporting was low. It might be necessary to raise awareness by actively soliciting reports from patients and caregivers.